2022
DOI: 10.2196/36018
|View full text |Cite
|
Sign up to set email alerts
|

Improving Well-being With a Mobile Artificial Intelligence–Powered Acceptance Commitment Therapy Tool: Pragmatic Retrospective Study

Abstract: Background Research and dissemination of smartphone apps to deliver coaching and psychological driven intervention had seen a great surge in recent years. Notably, Acceptance Commitment Therapy (ACT) protocols were shown to be uniquely effective in treating symptoms for both depression and anxiety when delivered through smartphone apps. The aim of this study is to expand on that work and test the suitability of artificial intelligence–driven interventions delivered directly through popular texting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
(26 reference statements)
0
1
0
Order By: Relevance
“…The results of this study provided us with significant evidence about the positive impact of digital technologies in mindfulness training for the development of self-regulation skills. However, some studies provided evidence for a significant improvement [105,106,125,139,140,145], whereas other studies indicated that the intervention had a positive but not significant impact on self-regulation or that more research with larger samples and longer periods of training was needed [36]. None of the selected studies showed that the employment of digitally assisted mindfulness harmed self-regulation.…”
Section: Final Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results of this study provided us with significant evidence about the positive impact of digital technologies in mindfulness training for the development of self-regulation skills. However, some studies provided evidence for a significant improvement [105,106,125,139,140,145], whereas other studies indicated that the intervention had a positive but not significant impact on self-regulation or that more research with larger samples and longer periods of training was needed [36]. None of the selected studies showed that the employment of digitally assisted mindfulness harmed self-regulation.…”
Section: Final Considerationsmentioning
confidence: 99%
“…A total sample of 10.387 adolescents were engaged with the conversational agent for an average of 45.39 days, showing significant improvements in mental and emotional balance. Kao.ai was also used in the research conducted by Naor et al [140]. An analysis of 2909 users of kai.ai indicated significant improvements in their ability to maintain their psychological health balance.…”
Section: Quality Of Studiesmentioning
confidence: 99%
“…User experience data collected from 13 adolescents in a one-session study of Beth Bot, a CBT-based chatbot for depression, suggests that some adolescents fnd mental health chatbots acceptable but that chatbots should be able to give personalized responses [11]. Kai.ai is a chatbot that has been designed with the broader aim of mental health promotion, utilizing ACT as well as adapting tools from positive psychology [38,50]. A longitudinal study over a period of four months indicated an increase in the well-being of participants, but the study did not provide insights into how or why the increase took place, and the disengagement from the use of Kai.ai was high [50].…”
Section: Conversational Interfaces For Mental Healthmentioning
confidence: 99%
“…As previously described, ACT aims to improve cognitive flexibility, as well as coping with challenging experiences, by focusing on cognitive diffusion, practicing mindfulness, and reflection on one’s values [ 22 , 23 ]. Kai.ai delivers the ACT intervention using an AI conversational bot that facilitates users in creating and enhancing habits for healthy living and resilience [ 24 ]. Kai.ai interacts with users throughout the day and leverages their responses to deliver a tailored ACT skilled coaching.…”
Section: Introductionmentioning
confidence: 99%